Związki frazeologiczne z komponentem bank w polszczyźnie - Ignatowicz-Skowrońska, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The subject of the article concerns phraseological units with the lexeme bank that can be found in the Polish language. The lexeme bank, which has been present in Polish since the sixteenth century, became the basis for a group of phraseological connections founded on three out of the four meanings of the word registered in dictionaries. More or less typically phraseological expressions were created around the meaning of the word bank as a money trading institution, or as a place where something is kept or stored and finally as a pot or pool in gambling games. The fourth meaning of bank, as an edifice that holds an institution involved in financial turnover, proved to be unattractive phraseologically and did not result in forming any phraseological units. Also it should be emphasized that some of the analyzed phraseological connections undergo semantic modifications in contemporary Polish, which have not yet been recorded in lexicographic collections. It happens so as new shades of meaning of the phrases rozbić bank (hit the jackpot) or trzymać bank (hold the pot) have not yet been fully established in the language and need to be carefully observed.